Native speakers' perceptions of fluency and accent in L2 speech. (July 2014) - Pinget, Anne-France; Bosker, Hans Rutger; Quené, Hugo; de Jong, Nivja H.
Oral fluency and foreign accent distinguish L2 from L1 speech production. In language testing practices, both fluency and accent are usually assessed by raters. This study investigates what exactly native raters of fluency and accent take into account when judging L2. Our aim is to explore the relationship between objectively measured temporal, segmental and suprasegmental properties of speech on the one hand, and fluency and accent as rated by native raters on the other hand. For 90 speech fragments from Turkish and English L2 learners of Dutch, several acoustic measures of fluency and accent were calculated. In Experiment 1, 20 native speakers of Dutch rated the L2 Dutch samples on fluency. In Experiment 2, 20 different untrained native speakers of Dutch judged the L2 Dutch samples on accentedness. Regression analyses revealed, first, that acoustic measures of fluency were good predictors of fluency ratings. Second, segmental and suprasegmental measures of accent could predict some variance of accent ratings. Third, perceived fluency and perceived accent were only weakly related. In conclusion, this study shows that fluency and perceived foreign accent can be judged as separate constructs.